Psoriasis Among Adolescents in Kuwait and the Role of Siblings, Breastfeeding, and Household Cat and Secondhand Smoke Exposure: A Cross-Sectional Study - Ali H. Ziyab; Wilfried Karmaus; Khadijah A. AlShatti; Manal Al-Kandari; Shaimaa H. Hussein; Yaser M. Ali (Adis, Springer Healthcare, 2020)
Abstract Introduction Globally, the epidemiology of psoriasis is poorly understood, and most countries lack essential epidemiologic data regarding disease burden and its determinants. This study sought to estimate the prevalence of psoriasis among adolescents in Kuwait and assess its association with different risk factors, including obesity, sibship size, breastfeeding, and exposure to household secondhand smoke (SHS) and pets. Methods Schoolchildren aged 11-14 years (n = 3864) were enrolled in a cross-sectional study. Lifetime and current (past 12 months) prevalence of psoriasis were ascertained according to ever having a history of doctor-diagnosis plus current active lesion(s) and/or current use of treatment of psoriasis. Associations were assessed using Poisson regression with robust variance estimation, and adjusted prevalence ratios (aPR) and 95% confidence intervals (CI) were estimated. Results The lifetime and current prevalence of psoriasis were estimated to be 3.6% (136/3806) and 1.1% (42/3806), respectively. Commonly reported anatomical sites affected by psoriasis included scalp (47.6%) and the extensor surface of the knees (50%) and elbows (38.1%). Household SHS exposure was associated with increased lifetime psoriasis (aPR = 1.41, 95% CI 1.07-1.98), and showed a trend for association with current psoriasis (1.77, 0.89-3.53). Similarly, cat-keeping during infancy was associated with lifetime psoriasis (1.96, 1.14-3.37), and demonstrated a trend for association with current psoriasis (1.49, 0.52-1.98). In contrast, breastfeeding was associated with a decreased lifetime psoriasis (0.62, 0.44-0.89), but was not associated with current psoriasis. Trend analyses showed that the prevalence of lifetime and current psoriasis increased with increasing numbers of total, older, and younger siblings. Conclusions Psoriasis affects a considerable proportion of schoolchildren in Kuwait. Interestingly, psoriasis prevalence was related to risk factors also found in allergic diseases, such as exposure to SHS, cat-keeping in infancy, breastfeeding, and sibship size, possibly suggesting a role of immune dysregulation.